Оптимізація цілеспрямованого пошуку скавенджерів NO в ряду похідних ксантину - Риженко, Віктор Павлович; Ryzhenko, V. P. (My University, 2020)
Вперше для оптимізації цілеспрямованого пошуку скавенджерів NO в ряду знову синтезованих сполук розроблена комп'ютерна програма віртуального скринінгу за допомогою алгоритмів машинного навчання з використанням моделі "градієнтного бустінга", використання якої дозволило виявити серед похідних ксантину − гідразид 8-бензиламінотеофілініл-7-оцтової кислоти (С-3) з властивостями скавенджера NO. Встановлено, що С-3 підвищує рівень GSH і HSP70 у суспензії нейронів в умовах нітрозативного стрессу in vitro. Вперше показано, що С-3 (100 мг/кг) на моделі інфаркту міокарда нормалізує експресію eNOS/iNOS, продукцію NO і активує малат-аспартатний човниковий механізм, а на моделі ВК гальмує експресію iNOS, відновлює SH/SS рівновагу, підвищує HSP70 і покращує показники пам'яті. С-3 підвищує толерантність до фізичних навантажень і покращує енергетичний метаболізм міокарда на моделі робочої гіпоксії. Встановлено перевагу С-3 перед мілдронатом, пірацетамом і мексидолом. Протиішемічна дія С-3 визначається її властивостями скавенджера NO і спрямована на переривання АФК/SH-залежних механізмів порушень енергетичного метаболізму і депривації системи ендогенної цитопротекції. The dissertation is devoted to the actual task of modern pharmacology − the search for new effective antioxidants among xanthine derivatives for use in the treatment of myocardial and cerebral ischemia. The work is carried out for evaluation of the antioxidant activity of 122 xanthine derivatives in vitro with respect to NO inhibition. The dependence of antioxidant activity on quantum chemical parameters of xanthine derivatives was analyzed using machine learning algorithms using the following models: Linear Regression, Support Vector Machine Regression, Random Forest Regression, Gradient Boosting Regression, K-Nearest Neighbors Regression. As a result of our analysis, we tested several models for solving regression problems. The best models without the use of optimization were the models of "Reference vectors" and "K-nearest neighbors". When optimizing the studied models, the best generalizing ability was shown by the "Gradient boosting" model with an error within 16%. This model can be used for the prediction of antioxidant activity based on quantum chemical parameters. Further improvement of the quality of the model is possible by increasing the training and test samples, as well as expanding the features to deepen the model and improve the generalization ability. A program of virtual screening of substances with the properties of NO scavengers has been developed and created. In the process of testing the new synthesized xanthine derivatives, a computer program made it possible to predict the most pronounced properties of the NO scavenger in 8-benzylaminotheophilinyl-7-acetic acid hydrazide (C-3). In vitro experiments confirmed the prediction of the properties of the NO scavenger in C-3 (267,3%). When simulating nitrosating stress (DNIC, 250 μM) in vitro, the introduction of C-3 in the incubation mixture (10-5M) leads to a decrease in nitrotyrosine by 45%, an increase in GSH by 43,8%, HSP70 by 34,7% and an increase in GPR activity at 337% and GR by 195%. (p<0,05) in a suspension of neurons.
Optimization of purposeful search of NO scavengers in a number of xanthine derivatives
Keywords: скавенджери NO; ішемія міокарда; внутрішньомозковий крововилив; комп'ютерна програма; віртуальний скринінг; похідні ксантину; xanthine derivatives; NO scavengers; antioxidant action; cerebral and myocardial ischemia; virtual screening; computer program